Manual pretreatment method for analyzing Bulk Cu and Ni in silicon wafer through PUTP method

The polycrystalline layer on the surface of the silicon wafer was etched by nitrogen-driven mixed acid corrosion liquid and recycled Bulk Cu/Ni was solved, and the operation difficulties and high cost problems of Bulk Cu and Ni in silicon wafers were solved by PUTP method, achieving accurate and effective analysis of Bulk Cu/Ni on silicon wafers.

CN119860966APending Publication Date: 2025-04-22杭州中欣晶圆半导体股份有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411972434.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing PUTP method analyzes Bulk Cu and Ni in silicon wafers with problems of operation difficulties, uneven corrosion and high cost, especially the manual pretreatment method lacks effective polycrystalline silicon corrosion and recycling technology.

Method used

The polycrystalline layer on the surface of the silicon wafer is etched by nitrogen-driven mixed acid corrosion liquid, and the manual pretreatment method is realized by recycling Bulk Cu/Ni that absorbs polycrystallines. This method uses mixed acid in a mass ratio of 55% to 70% HNO3:38% to 49% HF:H2O=1 to 5:1 to 5:1 to 4, and corrode the entire surface polycrystalline layer by driving droplets by nitrogen, and the corrosion liquid is recovered. After heating and evaporation, residual elements are extracted with the scanning liquid, and then sent to ICP-MS for analysis.

Benefits of technology

The PUTP method is used to accurately analyze silicon wafer Bulk Cu/Ni, which reduces analysis costs, avoids high cost investment in VPD automatic pretreatment devices, and can be quickly and batchly applied to the analysis of silicon wafer Bulk Cu/Ni in 100 crystalline directions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119860966A_ABST
    Figure CN119860966A_ABST
Patent Text Reader

Abstract

The invention relates to a manual pretreatment method for analyzing Bulk Cu and Ni in a silicon wafer through a PUTP method, and belongs to the technical field of silicon wafer detection. And depositing a polycrystalline layer on the polished wafer. And then the polycrystalline thickness on the surface of the polycrystalline thickness monitoring sheet is measured. Then preparing silicon corrosion mixed acid, and recording the initial mass amount H1, namely the bottle containing the PFA; taking out a polycrystalline sample wafer growing 50nm, and taking a mean value and recording the mean value as a front value of the silicon wafer; pouring 2-5g of prepared mixed acid into the edge area of the sample wafer; and weighing the small PFA bottle filled with the mixed acid again, and recording the residual mass H2-the PFA-containing bottle. Next, liquid drops rapidly expand and sweep over the surface of the silicon wafer; and driving the mixed acid liquid drops to corrode the whole silicon wafer polycrystal layer through nitrogen. And then recovering the mixed acid corrosion liquid drops into a PFA container, heating the PFA container to evaporate silicon, and finally extracting residual elements through scanning liquid to carry out ICP-MS (Inductively Coupled Plasma Mass Spectrometry) analysis. The method has the characteristics of being accurate and effective, being used for batch analysis, being free of high-cost investment of VPD, realizing uniform corrosion of polycrystalline silicon and reducing analysis cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicon wafer detection, and in particular to a manual pre-treatment method for realizing PUTP method analysis of BulkCu and Ni in silicon wafer. Background Art

[0002] The detection methods for Bulk Cu / Ni analysis of semiconductor silicon wafers using ICP-MS include dissolution method (Bulk Digestion), LTOD (Low Temprature Out-Diffusion) method and PUTP (Poly Silicon Ultra-trace Profiling) polysilicon ultra-trace analysis method.

[0003] There is not much information available on the PUTP method for analyzing bulk copper and nickel in silicon wafers. The main reference in China is the method introduced in "Silicon Wafer Semiconductor Material Technology" edited by Lin Mingxian in 1998 and reprinted in 2023: "Poly UTP (Ultratrace Profiling) method: mainly used to measure the metal elements Cu and Ni with faster diffusion speeds. The operation steps are as follows:

[0004] 1) First, a 50nm thick silicon polycrystalline layer is grown on the surface of the test piece at 620℃. During this process, Cu and Ni will diffuse into the polycrystalline layer and stay in the polycrystalline (by virtue of the adsorption of defects at the grain boundaries).

[0005] 2) Then, a mixed acid of HF and HNO3 is used to etch away the surface of the polycrystalline layer, and the etching solution is then placed in a PFA beaker.

[0006] 3) Place the PFA beaker on a hotplate and heat it to evaporate the etching solution, leaving some solid residue in the beaker.

[0007] 4) Then, the solid residue is re-dissolved and diluted using a mixed acid of HF and HNO3 of a certain concentration.

[0008] 5) These solutions can then be analyzed for Cu and Ni concentrations using ICP-MS.

[0009] The detection limit of Poly UTP is about 5E9Atoms / cm2. It usually takes more than 2 days to complete both sides of a test piece.

[0010] The Poly UTP method briefly described has great difficulties in actual implementation. First, the method does not define the ratio of the mixed acid; second, after the HF and HNO3 mixed acid is added to the surface of the silicon wafer, an exothermic reaction of silicon etching will occur. As the reaction proceeds, the temperature of the mixed acid rises, and the intensity of the reaction increases, resulting in an uncontrolled rate and difficulty in ensuring corrosion uniformity; third, the mixed acid has a low selectivity for etching polysilicon and silicon, and it is difficult to control etching of only polysilicon and not silicon; the etching reaction will go from polysilicon to silicon, and how to control the mixed acid to uniformly etch the entire silicon wafer surface instead of etching in the depth direction is a difficult problem.

[0011] The application of VPD (chemical vapor digestion) equipment, an automatic silicon wafer pre-treatment device, has effectively solved the problem of polysilicon etching: by passing HF and HNO3 gas or HF and O3 into a closed chamber, polysilicon and silicon are decomposed to a certain depth, and then the metal on the surface of the silicon wafer is extracted and analyzed. The VPD method has improved the polycrystalline etching method that used HF and nitric acid etching liquid more than 20 years ago, and can obtain a fairly uniform etching depth and uniformity. However, the equipment and maintenance costs of the automatic pre-treatment device are extremely high, resulting in a high cost for bulk Cu / Ni testing of a single sample. Summary of the invention

[0012] The present invention mainly solves the deficiencies in the prior art and provides a manual pre-treatment method for realizing the PUTP method to analyze Bulk Cu and Ni in silicon wafers. The pre-treatment method uses nitrogen to drive mixed acid etching liquid to etch polycrystalline silicon wafer surface, extract Bulk Cu / Ni impurities into polycrystalline, and has no significant difference with the existing VPD pre-treatment method. The Cu / Ni elements obtained by ICP-MS analysis are accurate and effective, can be used for batch analysis without the high cost of VPD, realize uniform corrosion of polycrystalline silicon and reduce analysis costs.

[0013] The above technical problems of the present invention are mainly solved by the following technical solutions:

[0014] A manual pre-treatment method for analyzing Cu and Ni in silicon wafers by PUTP method comprises the following steps:

[0015] Step 1: Prepare materials, tools and experiments, and prepare several clean 100 crystal polished wafers.

[0016] Step 2: The polished wafer is placed in an LPCVD furnace at 600-700°C to deposit a polycrystalline layer of about 50nm. When depositing polysilicon, an oxide wafer with a similar doping surface growth of about 100nm is placed as a polycrystalline thickness monitoring wafer.

[0017] Step 3: Use an ellipsometer to measure the polycrystalline thickness on the surface of the polycrystalline thickness monitoring film, which is required to meet 50nm±5nm.

[0018] Step 4: Use 55%-70% HN03: 38%-49% HF: H20 = 1-5: 1-5: 1-4 mass ratio, and use electronic balance weighing method to prepare silicon corrosion mixed acid; after the mixed acid is prepared, weigh it using an electronic balance and record the initial mass H1-containing PFA bottle.

[0019] Step 5: Use vacuum cleaning in a fume hood to take out the grown 50nm polycrystalline sample, weigh it on an electronic balance, weigh it 3 times, and take the average value and record it as the pre-silicon wafer value.

[0020] Step 6: Place the weighed sample on the holder with a vacuum pen, and pour 2-5g of the prepared mixed acid into the edge of the sample; weigh the PFA vial containing the mixed acid again, and record the remaining mass H2-containing PFA bottle, where H2-H1 is the mass of the mixed acid H3 used for etching the sample;

[0021] Step 7: The surface of the polycrystalline layer is a natural oxide layer. The HF in the poured mixed acid first reacts with the natural oxide layer on the surface of the sample 4HF+SiO2=SiF4+H20. The droplets quickly expand and sweep across the surface of the silicon wafer, and then gather at the edge of the other end of the sample.

[0022] Step 8: After the droplets stagnate for a few seconds, they begin to corrode the polysilicon layer, and bubbles are generated; after the polycrystalline is corroded, the head of the droplet flows to the uncorroded area and forms small yellow bubbles, and the tail stays in the original place and corrodes in the depth direction and produces fine white bubbles; adjust the nitrogen gun to a suitable flow rate, and use nitrogen to drive the entire mixed acid droplet to flow to the uncorroded polycrystalline layer area along the flow direction of the droplet for corrosion until the polycrystalline on the entire silicon wafer surface is completely corroded; polysilicon corrosion reaction formula: 3Si(s)+4HNO3(aq)+18HF(aq)=3H2SiF6+4NO(gas)+8H2O;

[0023] Step 9: Use a vacuum pen to suck up the silicon wafer, pour the corroded liquid droplets into a clean PFA bottle, weigh the weight of the vial before and after, and obtain the mass of the recovered corrosive liquid H4; H4 divided by H3 in step 6 is the recovery rate of the mixed acid corrosive liquid, which is required to be >80%;

[0024] Step 10: Use a pipette to transfer 1-10 ml of scanning liquid, scan the entire silicon wafer surface again, recover the residual liquid and elements on the silicon wafer surface, and pour them into the PFA bottle containing the recovered mixed acid;

[0025] Step 11: Wash and dry the sample after etching, and weigh it again with an electronic balance for 3 times to obtain the post-wafer value B; the post-wafer value B minus the pre-wafer value A of the silicon wafer is the silicon mass of this mixed acid etching; thus, the overall average corrosion depth of the sample is calculated, which is required to be less than 0.1μm;

[0026] Step 12: Pour 1-10g of mixed acid and 1-10ml of scanning solution into another PFA bottle as a blank sample;

[0027] Step 13: Place the addition plate in a fume hood, and heat the PFA bottles containing the samples and the blank samples at 100°C to 200°C until solid crystals are left at the bottom of the bottles;

[0028] Step 14: Add scanning extraction solution into the PFA bottle and shake to dissolve the solid crystals to obtain a clear liquid, which is then analyzed using ICP-MS.

[0029] Preferably, the pretreatment and analysis process needs to be performed in a Class 100 or higher clean room environment, and the pretreatment work is completed in a fume hood, which requires a Class 10 dust-free internal environment.

[0030] Preferably, the fume hood is cleaned and washed, free from metal, glass and other material contamination; the clean fume hood is tested to have a particle size ≥ 0.5 μm and air particles above ≤ 1; the exhaust is sufficient and the fume hood is in a negative pressure state.

[0031] Preferably, prepare UPSSS grade 55% to 70% nitric acid, requiring metal elements ≤10ppt; UPSSS grade 38 to 49% hydrofluoric acid, requiring metal elements ≤10ppt; UPSSS grade 30 to 35% hydrogen peroxide, requiring metal elements ≤10ppt; prepare several 100ml clean PFA volumetric flasks, soak them in 50 to 100°C 3% to 10% nitric acid for 12 hours or more, ICP-MS analysis shows that the metal content of nitric acid after soaking is <1ppt, pour out the nitric acid, wash more than 6 PFA volumetric flasks with ultrapure water for standby use; use 100ml PFA sample bottles to prepare 20% to 49% hydrofluoric acid solution and 2 to 10% HF + 2 to 10% H2O2 extraction scanning solution, ICP-MS analysis shows that the metal elements are ≤1ppt for standby use.

[0032] Preferably, clean special acid-proof gloves, acid-proof aprons, helmets and acid-proof boots and keep them ready for use; clean the heating plate and place it in the fume hood; clean the process nitrogen gun, and the process nitrogen requires 5N to 9N and keep it ready for use; clean the vacuum suction pen and keep it ready for use; prepare a clean 100-1000μl pipette and keep it ready for use; prepare an electronic balance with an accuracy of 0.0001g, adjust it and keep it ready for use.

[0033] Preferably, under the action of high temperature in the LPCVD furnace tube, the fast-diffusing Cu / Ni metal in the silicon wafer body diffuses to the polycrystalline layer on the surface of the silicon wafer, sinks into the grain boundary of the polycrystalline, and is thus fixed in the polycrystalline layer.

[0034] As a preferred method, the accuracy of the pre-treatment method is verified: 1) LPCVD grows a 50nm polycrystalline layer sample, divides it into several pieces, uses VPD to dry etch to a suitable depth using HF and O3 gases, and dries at 100℃~150℃ to remove silicon; 2) The surface of the silicon wafer after dry etching is scanned and extracted by scanning extraction liquid; 3) ICP-MS analysis of the extraction liquid; 4) Compare the Cu / Ni data of the samples analyzed after manual pre-treatment and VPD automatic pre-treatment.

[0035] The present invention can achieve the following effects:

[0036] The present invention provides a manual pre-treatment method for realizing PUTP method analysis of Bulk Cu and Ni in silicon wafers. Compared with the prior art, the pre-treatment method adopts nitrogen to drive mixed acid etching liquid to etch polycrystalline on the surface of silicon wafers, and recovers Bulk Cu / Ni adsorbed to polycrystalline. Compared with the existing VPD pre-treatment method, there is no significant difference in Cu / Ni elements obtained by ICP-MS analysis. It is accurate and effective, can be used for batch analysis without high cost investment of VPD, realizes uniform corrosion of polycrystalline silicon and reduces analysis cost.

[0037] The mixed acid etching solution with appropriate proportion of HNO3, HF and H2O is used to etch the polycrystalline layer on the entire wafer surface by nitrogen-driven droplets, and the etching solution is recovered, heated and evaporated to drive away silicon, and then the residual elements are extracted with scanning liquid, and then sent to ICP-MS analysis to realize the PUTP method for BulkCu / Ni analysis of silicon wafers. The nitrogen-driven method solves the problem of uniform corrosion of the entire polycrystalline surface of silicon wafers and is applied to batch analysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a process flow chart of the present invention.

[0039] Figure 2 It is a comparison chart of Bulk Cu content between manual pre-treatment and VPD pre-treatment of the present invention.

[0040] Figure 3 It is a comparison chart of Bulk Ni content between manual pretreatment and VPD pretreatment of the present invention. DETAILED DESCRIPTION

[0041] The technical solution of the invention is further specifically described below through embodiments and in conjunction with the accompanying drawings.

[0042] Example: Figure 1 , Figure 2 and Figure 3 As shown, a manual pre-treatment method for analyzing Bulk Cu and Ni in silicon wafers by PUTP method includes the following steps:

[0043] Step 1: Prepare materials, tools and experiments, and prepare several clean 100 crystal polished wafers.

[0044] The pre-treatment and analysis process needs to be in a Class 100 or higher clean room environment. The pre-treatment work is completed in a fume hood, which requires a Class 10 dust-free environment. The fume hood is cleaned and washed, free of metal, glass and other material pollution; the clean fume hood detects air particles with a diameter of ≥ 0.5μm and above, and ≤ 1; the exhaust is sufficient, and the fume hood is in a negative pressure state.

[0045] Prepare UPSSS grade 55%-70% nitric acid, requiring metal elements ≤10ppt; UPSSS grade 38-49% hydrofluoric acid, requiring metal elements ≤10ppt; UPSSS grade 30-35% hydrogen peroxide, requiring metal elements ≤10ppt; prepare several 100ml clean PFA volumetric flasks, soak them in 50 to 100℃ 3%-10% nitric acid for 12 hours or more, ICP-MS analysis shows that the metal content of nitric acid after soaking is <1ppt, pour out the nitric acid, wash the PFA volumetric flasks with ultrapure water for more than 6 times and keep them for use; use 100ml PFA sample bottles to prepare 20%-49% hydrofluoric acid solution and 2-10% HF+2-10% H2O2 extraction scanning solution, ICP-MS analysis shows that the metal elements are ≤1ppt and keep them for use.

[0046] Clean special acid-proof gloves, acid-proof aprons, helmets and acid-proof boots and keep them ready for use; clean the heating plate and place it in the fume hood; clean the process nitrogen gun, the process nitrogen requires 5N to 9N and keep it ready for use; clean the vacuum suction pen and keep it ready for use; prepare a clean 100-1000μl pipette and keep it ready for use; prepare an electronic balance with an accuracy of 0.0001g, adjust it and keep it ready for use.

[0047] Step 2: The polishing sheet is placed in the LPCVD furnace tube at a temperature of 600-700℃ to deposit a polycrystalline layer of about 50nm. When depositing polycrystalline silicon, a similar doped surface oxide sheet with a thickness of about 100nm is placed as a polycrystalline thickness monitoring sheet. Under the action of the high temperature in the LPCVD furnace tube, the fast-diffusion Cu / Ni metal in the silicon wafer diffuses into the polycrystalline layer on the surface of the silicon wafer, sinks into the grain boundary of the polycrystalline, and is thus fixed in the polycrystalline layer.

[0048] Step 3: Use an ellipsometer to measure the polycrystalline thickness on the surface of the polycrystalline thickness monitoring film, which is required to meet 50nm±5nm.

[0049] Step 4: Use 55%-70% HNO3: 38%-49% HF: H2O = 1-5: 1-5: 1-4 mass ratio, and use electronic balance weighing method to prepare silicon corrosion mixed acid; after the mixed acid is prepared, weigh it using an electronic balance and record the initial mass H1-containing PFA bottle.

[0050] Step 5: Use vacuum cleaning in a fume hood to take out the grown 50nm polycrystalline sample, weigh it on an electronic balance, weigh it 3 times, and take the average value and record it as the pre-silicon wafer value.

[0051] Step 6: Place the weighed sample on the holder with a vacuum pen, and pour 2-5g of the prepared mixed acid into the edge of the sample; weigh the PFA vial containing the mixed acid again, and record the remaining mass H2-containing PFA bottle, where H2-H1 is the mass of the mixed acid H3 used for etching the sample;

[0052] Step 7: The surface of the polycrystalline layer is a natural oxide layer. The HF in the poured mixed acid first reacts with the natural oxide layer on the surface of the sample 4HF+SiO2=SiF4+H20. The droplets quickly expand and sweep across the surface of the silicon wafer, and then gather at the edge of the other end of the sample.

[0053] Step 8: After the droplets stagnate for a few seconds, they begin to corrode the polysilicon layer, and bubbles are generated; after the polycrystalline is corroded, the head of the droplet flows to the uncorroded area and forms small yellow bubbles, and the tail stays in the original place and corrodes in the depth direction and produces fine white bubbles; adjust the nitrogen gun to a suitable flow rate, and use nitrogen to drive the entire mixed acid droplet to flow to the uncorroded polycrystalline layer area along the flow direction of the droplet for corrosion until the polycrystalline on the entire silicon wafer surface is completely corroded; polysilicon corrosion reaction formula: 3Si(s)+4HNO3(aq)+18HF(aq)=3H2SiF6+4NO(gas)+8H2O;

[0054] Step 9: Use a vacuum pen to suck up the silicon wafer, pour the corroded liquid droplets into a clean PFA bottle, weigh the weight of the vial before and after, and obtain the mass of the recovered corrosive liquid H4; H4 divided by H3 in step 6 is the recovery rate of the mixed acid corrosive liquid, which is required to be >80%;

[0055] Step 10: Use a pipette to transfer 1-10 ml of scanning liquid, scan the entire silicon wafer surface again, recover the residual liquid and elements on the silicon wafer surface, and pour them into the PFA bottle containing the recovered mixed acid;

[0056] Step 11: Wash and dry the sample after etching, and weigh it again with an electronic balance for 3 times to obtain the post-wafer value B; the post-wafer value B minus the pre-wafer value A of the silicon wafer is the silicon mass of this mixed acid etching; thus, the overall average corrosion depth of the sample is calculated, which is required to be less than 0.1μm;

[0057] Step 12: Pour 1-10g of mixed acid and 1-10ml of scanning solution into another PFA bottle as a blank sample;

[0058] Step 13: Place the addition plate in a fume hood, and heat the PFA bottles containing the samples and the blank samples at 100°C to 200°C until solid crystals are left at the bottom of the bottles;

[0059] Step 14: Add scanning extraction solution into the PFA bottle and shake to dissolve the solid crystals to obtain a clear liquid, which is then analyzed using ICP-MS.

[0060] The accuracy of the pre-treatment method was verified: 1) The samples of 50nm polycrystalline layer grown by LPCVD were divided into several pieces, and dry-etched to a suitable depth using HF and O3 gases by VPD, and dried at 125℃ to remove silicon; 2) The surface of the silicon wafer after dry etching was scanned and extracted by scanning extraction liquid; 3) ICP-MS analysis of the extraction liquid; 4) Comparison of Cu / Ni data of samples analyzed after manual pre-treatment and VPD automatic pre-treatment.

[0061] Two-Sample T-Test and Confidence Intervals: Cu-Manual Pre-Processing, Cu-VPD Processing

[0062] Cu-manual pre-treatment and Cu-VPD treatment double sample T

[0063]

[0064] Difference = μ(Cu-manual pre-treatment)-μ(Cu-VPD treatment)

[0065] Difference estimate: 0.0367

[0066] 95% confidence interval for the difference: (-0.0188, 0.0921)

[0067] T-test for difference = 0 (≠): T value = 1.42 P value = 0.178 degrees of freedom = 14

[0068] from Figure 1 Comparing the Bulk Cu content, the double sample test between manual pretreatment and VPD pretreatment was within the 95% confidence interval, P=0.187>0.05, and there was no significant difference between the two.

[0069] Two-Sample T-Test and Confidence Intervals: Ni-Manual Pre-Processing, Ni-VPD Processing

[0070] Ni-manual pre-treatment and Ni-VPD treatment double sample T

[0071]

[0072] Difference = μ(Ni-manual pre-treatment)-μ(Ni-VPD treatment)

[0073] Difference estimate: 0.0128

[0074] 95% confidence interval for the difference: (-0.0536, 0.0793)

[0075] T-test for difference = 0 (≠): T value = 0.61 P value = 0.582 degrees of freedom = 3

[0076] from Figure 2 Comparing the Bulk Ni content, the double sample test between manual pre-treatment and VPD pre-treatment had no significant difference within the 95% confidence interval, P value = 0.582 > 0.05.

[0077] In summary, the manual pretreatment method for realizing the PUTP method for analyzing Bulk Cu and Ni in silicon wafers is to add a mixed acid silicon etching solution with a mass ratio of 55% to 70% HNO3: 38% to 49% HF: H2O = 1 to 5: 1 to 5: 1 to 4 directly to the polycrystalline layer on the surface of the silicon wafer, and then the entire polycrystalline layer on the surface of the silicon wafer is etched by nitrogen-driven droplets at an appropriate time, and then the etching solution is collected in a PFA container, and then the silicon is driven out by heating the container, and the pretreatment method of extracting the residual elements after heating is consistent with the VPD pretreatment analysis result. The PUTP method is used to analyze Bulk Cu / Ni on silicon wafers manually. Compared with the VPD automatic pretreatment method, the manual pretreatment method of the present invention greatly reduces the detection cost, improves the detection speed, and can be quickly and batch-applied to the analysis of Bulk Cu / Ni on silicon wafers with 100 crystal orientations.

[0078] The above description is only a specific embodiment of the present invention, but the structural features of the present invention are not limited thereto. Any changes or modifications made by any technician in the field of the present invention are included in the patent scope of the present invention.

Claims

1. A manual pre-treatment method for analyzing Bulk Cu and Ni in silicon wafers by PUTP method, characterized in that The steps are as follows: Step 1: Prepare materials, tools and experiments, and prepare several clean 100 crystal polished wafers; Step 2: The polished sheet is placed in a LPCVD furnace at 600-700°C to deposit a polycrystalline layer of about 50nm. When depositing polysilicon, an oxide sheet with a surface growth of about 100nm of the same doping is placed as a polycrystalline thickness monitoring sheet. Step 3: Use an ellipsometer to measure the polycrystalline thickness on the surface of the polycrystalline thickness monitoring film, which is required to meet 50nm±5nm; Step 4: Use 55% to 70% HN03: 38% to 49% HF: H20 = 1 to 5: 1 to 5: 1 to 4 mass ratio, and use the electronic balance weighing method to prepare the silicon corrosion mixed acid; after the mixed acid is prepared, weigh it using an electronic balance and record the initial mass H1-containing PFA bottle; Step 5: Use vacuum cleaning in a fume hood to take out the 50nm polycrystalline sample, weigh it on an electronic balance, weigh it 3 times, and take the average value as the pre-silicon value; Step 6: Place the weighed sample on the holder with a vacuum pen, and pour 2-5g of the prepared mixed acid into the edge of the sample; weigh the PFA vial containing the mixed acid again, and record the remaining mass H2-containing PFA bottle, where H2-H1 is the mass of the mixed acid H3 used for etching the sample; Step 7: The surface of the polycrystalline layer is a natural oxide layer. The HF in the poured mixed acid first reacts with the natural oxide layer on the surface of the sample to form 4HF+SiO2=SiF4+H20. The droplets quickly spread across the surface of the silicon wafer and then gather at the edge of the other end of the sample. Step 8: After the droplets stagnate for a few seconds, they begin to corrode the polysilicon layer, and bubbles are generated; after the polycrystalline is corroded, the head of the droplet flows to the uncorroded area and forms small yellow bubbles, and the tail stays in the original place and corrodes in the depth direction and produces fine white bubbles; adjust the nitrogen gun to a suitable flow rate, and use nitrogen to drive the entire mixed acid droplet to flow to the uncorroded polycrystalline layer area along the flow direction of the droplet for corrosion until the polycrystalline on the entire silicon wafer surface is completely corroded; polysilicon corrosion reaction formula: 3Si(s)+4HNO3(aq)+18HF(aq)=3H2SiF6+4NO(gas)+8H2O; Step 9: Use a vacuum pen to suck up the silicon wafer, pour the corroded liquid droplets into a clean PFA bottle, weigh the weight of the vial before and after, and obtain the mass of the recovered corrosive liquid H4; H4 divided by H3 in step 6 is the recovery rate of the mixed acid corrosive liquid, which is required to be >80%; Step 10: Use a pipette to transfer 1-10 ml of scanning liquid, scan the entire silicon wafer surface again, recover the residual liquid and elements on the silicon wafer surface, and pour them into the PFA bottle containing the recovered mixed acid; Step 11: Wash and dry the sample after etching, and weigh it again with an electronic balance for 3 times to obtain the post-wafer value B; the post-wafer value B minus the pre-wafer value A of the silicon wafer is the silicon mass of this mixed acid etching; thus, the overall average corrosion depth of the sample is calculated, which is required to be less than 0.1μm; Step 12: Pour 1-10g of mixed acid and 1-10ml of scanning solution into another PFA bottle as a blank sample; Step 13: Place the addition plate in a fume hood, and heat the PFA bottles containing the samples and the blank samples at 100°C to 200°C until solid crystals are left at the bottom of the bottles; Step 14: Add scanning extraction solution into the PFA bottle and shake to dissolve the solid crystals to obtain a clear liquid, which is then analyzed using ICP-MS.

2. The manual pre-treatment method for analyzing Bulk Cu and Ni in silicon wafers by PUTP method according to claim 1, characterized in that: The pre-treatment and analysis process needs to be in a clean room environment of Class 100 or above. The pre-treatment work is completed in a fume hood, and the fume hood requires a Class 10 dust-free environment.

3. The manual pre-treatment method for analyzing Bulk Cu and Ni in silicon wafers by PUTP method according to claim 2, characterized in that: The fume hood has been cleaned and washed, with no contamination from materials such as metal and glass; the clean fume hood has been tested to have a particle size ≥ 0.5μm and air particles above ≤ 1; the exhaust is sufficient and the fume hood is in a negative pressure state.

4. The manual pre-treatment method for analyzing Bulk Cu and Ni in silicon wafers by PUTP method according to claim 1, characterized in that: Prepare UPSSS grade 55%-70% nitric acid, requiring metal elements ≤10ppt; UPSSS grade 38-49% hydrofluoric acid, requiring metal elements ≤10ppt; UPSSS grade 30-35% hydrogen peroxide, requiring metal elements ≤10ppt; prepare several 100ml clean PFA volumetric flasks, soak them in 50 to 100℃ 3%-10% nitric acid for 12 hours or more, ICP-MS analysis shows that the metal content of nitric acid after soaking is <1ppt, pour out the nitric acid, wash the PFA volumetric flasks with ultrapure water for more than 6 times and keep them for use; use 100ml PFA sample bottles to prepare 20%-49% hydrofluoric acid solution and 2-10% HF+2-10% H2O2 extraction scanning solution, ICP-MS analysis shows that the metal elements are ≤1ppt and keep them for use.

5. The manual pre-treatment method for realizing PUTP analysis of Bulk Cu and Ni in silicon wafers according to claim 1, characterized in that: Clean special acid-proof gloves, acid-proof aprons, helmets and acid-proof boots for use; clean heating plates and place them in the fume hood; Clean the process nitrogen gun, the process nitrogen requires 5N to 9N for backup; clean the vacuum pen for backup; prepare a clean 100-1000μl pipette for backup; prepare an electronic balance with an accuracy of 0.0001g, adjust it and use it.

6. The manual pre-treatment method for analyzing Bulk Cu and Ni in silicon wafers by PUTP method according to claim 1, characterized in that: Under the action of high temperature in the LPCVD furnace tube, the fast-diffusing Cu / Ni metal in the silicon wafer diffuses to the polycrystalline layer on the surface of the silicon wafer, sinks into the grain boundary of the polycrystalline, and is thus fixed in the polycrystalline layer.

7. The manual pre-treatment method for analyzing Bulk Cu and Ni in silicon wafers by PUTP method according to claim 1, characterized in that The accuracy of the pre-treatment method was verified: 1) The samples of 50nm polycrystalline layer grown by LPCVD were divided into several pieces, and dry-etched to a suitable depth using HF and 03 gases by VPD, and dried at 100℃~150℃ to remove silicon; 2) The surface of the silicon wafer after dry etching was scanned and extracted by scanning extraction liquid; 3) ICP-MS analysis of the extraction liquid; 4) Comparison of Cu / Ni data of samples analyzed after manual pre-treatment and VPD automatic pre-treatment.